An analysis of the variables that impact the preparedness of parents to release their premature babies from the hospital - He, Ting; Sa'at, Siti Fatimah; Tang, Li Hua (IIUM Press, 2024)
Background: The thorough preparation of preterm babies for release home is strongly linked to the decision-making process about their discharge and has a significant impact on their health outcomes. It is crucial in facilitating a seamless transition from the hospital to their home environment.